2013
DOI: 10.5223/pghn.2013.16.3.162
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Role of Viral Isolates from Stool Samples of Intussuception in Children

Abstract: PurposeTo detect major acute gastroenteritis virus (rotavirus, norovirus, astrovirus, and enteric adenovirus) and non-enteric type of adenovirus (AdV) in the stools of intussusception patients and to investigate the clinical role of detected viruses.MethodsFrom March 2012 to February 2013, major acute gastroenteritis virus and non-enteric type of AdV were isolated from stool samples that collected from 44 patients treated for intussusception in Chungnam National University Hospital. Patients were divided accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…Several other studies have shown that adenoviruses are the viruses predominantly detected in intussusception ( 3 10 11 12 17 18 19 ). In this study, adenoviruses were the pathogens predominantly associated with intussusception, and were detected significantly more often in patients with intussusception than in the controls (42.1% vs. 12.3%, P < 0.001) ( Table 2 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Several other studies have shown that adenoviruses are the viruses predominantly detected in intussusception ( 3 10 11 12 17 18 19 ). In this study, adenoviruses were the pathogens predominantly associated with intussusception, and were detected significantly more often in patients with intussusception than in the controls (42.1% vs. 12.3%, P < 0.001) ( Table 2 ).…”
Section: Discussionmentioning
confidence: 97%
“…Our results show that 96.3% (51/53) of the adenovirus associated with intussusception were NEAds. Intussusception has been particularly associated with adenoviral types 1, 2, 5, and 6, all belonging to NEAd subgroup C ( 3 19 29 30 ). In our adenoviral subgroup analysis, the predominant subgroup was also adenoviral subgroup C, and 45.1% (23/51) of the NEAds detected were subgroup C in the NEAd-positive patients with intussusception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the relationship of HAstV infection to the etiology of intussusception in children has also been studied. Although with less frequency than rotavirus, norovirus, and adenovirus infection, HAstV infection has also been identified as a potential risk factor for intussusception in infected children (101)(102)(103).…”
Section: Clinical Disease Correlatesmentioning
confidence: 99%
“…Although the pathogenic mechanism of intussusception without leading points has not yet been clarifi ed, its major cause is suggested to be swelling and lymph node hyperplasia of Peyer's patch in the ileum secondary to infection [8]. Viral infections play a pivotal role in the etiology of invagination [9]. Invagination was seen after prolonged diarrhea in presented patient and any etiologic agent, such as adenovirus and rotavirus, was not detected.…”
Section: Discussionmentioning
confidence: 84%